Identification of Homogeneous Areas for Drought Frequency Analysis - Rahmat, Siti Nazahiyah; Jayasuriya, Niranjali; Bhuiyan, Muhammed (International Journal of Integrated Engineering, 2017)
Owing to high spatial and temporal rainfall variability, rationale water management decision-making is complex. Hence, it is essential to identify homogeneous areas to assist water management. This paper focusses on separating the study area into homogeneous groups to predict the risk of occurrence of a drought event. The severity-duration-frequency (SDF) curves were developed to determine the relationship between the probability of a drought occurring with a certain severity and frequency at the selected stations in Victoria, Australia. Two techniques namely cluster analysis and modified Andrews curve were used in grouping study area that have similar climate characteristics with respect to risk of occurrence of drought (i.e. rainfall variability). The study area was divided into six clusters and they adequately covered the study area. A mean drought frequency curve was developed for each homogeneous group to determine the probability of vulnerability to a drought event with a certain severity. The advantage of separating stations into homogenous groups based on similar drought characteristics is that it eliminates the necessity to carry out a detailed drought characteristic analysis for any location of interest. The measurable characteristics of this station will determine its best match with the existing cluster groups.